2019
DOI: 10.3390/fire2020026
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Influence of Local Social Context on Strategies for Achieving Fire Adapted Communities

Abstract: There is a growing recognition that the social diversity of communities at risk from wildland fire may necessitate divergent combinations of policies, programs and incentives that allow diverse populations to promote fire adapted communities (FACs). However, there have been few coordinated research efforts to explore the perceived utility and effectiveness of various options for FACs among residents, professionals, and local officials in disparate communities with different social contexts. The research presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 86 publications
(188 reference statements)
0
23
0
Order By: Relevance
“…Our study sample frame focused on two populations that have recently experienced fire; therefore, their responses may be different from those of other WUI communities where fire has not occurred, or occurred more than two or three years ago. Numerous researchers highlight that WUI communities are socially diverse (e.g., [54,55]), and we hope that future research can advance understandings of how different WUI populations may respond and recover at the wildfire-pandemic interface. Additionally, both study areas are rural, and may not necessarily reflect how urban populations, or the population of Arizona more broadly, might respond to concurrent hazards.…”
Section: Discussionmentioning
confidence: 99%
“…Our study sample frame focused on two populations that have recently experienced fire; therefore, their responses may be different from those of other WUI communities where fire has not occurred, or occurred more than two or three years ago. Numerous researchers highlight that WUI communities are socially diverse (e.g., [54,55]), and we hope that future research can advance understandings of how different WUI populations may respond and recover at the wildfire-pandemic interface. Additionally, both study areas are rural, and may not necessarily reflect how urban populations, or the population of Arizona more broadly, might respond to concurrent hazards.…”
Section: Discussionmentioning
confidence: 99%
“…A discussion of adaptation in the WUI must begin with an acknowledgement of social complexity resulting from the many differences among WUI communities located across a diverse biophysical landscape [18,37,39]. Local social context is dependent on the various social, biophysical, and historical characteristics that are specific to a particular community [40]. Adding to the complexity is the fact that those characteristics are not stagnant, but rather are in a near-constant state of flux [14,23].…”
Section: Literaturementioning
confidence: 99%
“…Research on social context and specific pathway approaches demonstrated, for example, that communities that are traditionally resource-dependent or working landscape communities [5] may have a better chance of reducing wildfire risk if they were given funds to self-organize volunteer firefighting and hazard mitigation capacity while a different type of community, formalized subdivisions, may require hired contractors or professionals to carry out these functions. Similarly, educational/outreach programs couched in formal scientific language may resonate among residents of a formal subdivision while messages framed in terms of the practical experience of longtime practitioners may find greater receptivity among more rural residents [1,13,40]. Just as each community type has pathways that have a better chance of succeeding, they also have barriers to success that are unique to their community type.…”
Section: Pathways and Barriersmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the understanding of the interconnections between fire regimes and landscape changes can inform fire managers on the likely effects of altering fire regimes on the landscape and inform landscape planners on the likely effect of altering landscapes on the fire regimes. The local impacts of different historical fire management policies, historical land management policies and historical protection guidelines, as well as the phenomena of the rural exodus and land abandonment in each of these two inner mountain areas are definitely worth to explore in order to better understand the disparity of fire occurrence in these two case study areas [14,49,89,128,129].…”
Section: Value Limitations and Future Researchmentioning
confidence: 99%